Spatio-temporal droplet size statistics in developing spray of starchy solution - Naz, M.Y. (American Institute of Physics Inc., 2015)
In the given research, the spray jet breakup of a modified starch solution was studied as a function of jet injection time and nozzle orifice diameter. The starch-urea-borax solution was prepared and tested with three axisymmetric full cone nozzles at service temperature of 80Â°C and the injection pressure of 5 bar. It is worth mentioning that no jet breakup was seen below these temperature and pressure values. The imaging studies on the time based spray evolution revealed monotonic increase in both; spray cone angle and tip penetration with an increase in injection time form 0-300 mm. Hereinafter, both parameters exhibited constants value over injection time. Phase Doppler Anemometry (PDA) measurements of the droplet size revealed significant decrease in the Sauter Mean Diameter (SMD) along the spray centerline. However, a steady decrease in SMD was seen towards the spray boundary. For fixed injection time of 300 ms, the overall SMD was decreased from 112 to 71 Î¼m at 60 mm downstream, from 102 to 64 Î¼m at 100 mm downstream and from 85 to 61 Î¼m at 140 mm downstream with an increase in orifice diameter from 1.19 to 1.59 mm. Â© 2015 AIP Publishing LLC.